Māori Experiences and Beliefs about Antibiotics and Antimicrobial Resistance for Acute Upper Respiratory Tract Symptoms: A Qualitative Study - Kayla Hika; Matire Harwood; Stephen Ritchie; Amy Hai Yan Chan (MDPI AG, 2022)
Antimicrobial resistance (AMR) is a threat to public health. Addressing unnecessary antibiotic use provides an opportunity to reduce antibiotic consumption and to slow AMR. Understanding people's beliefs is important for informing antimicrobial stewardship (AMS) initiatives. Within New Zealand, health inequities exist between Māori and non-Māori; however, no research has examined Māori beliefs about antibiotics and AMR. The aim of this study was to explore the experiences related to antibiotic use of Māori in New Zealand. In-depth, semi-structured interviews were conducted with 30 Māori adults recruited from primary care to explore the experiences, perceptions and beliefs that Māori have about antibiotics, and about AMR. Overall, 30 Māori adults (23% male; age range from 20 to 77 years) participated. Three themes emerged: systemic-, social-, and individual-related factors. From these themes, seven subthemes explained the factors that influenced antibiotic use and their perceptions of AMR in Māori: general practitioner (GP) times and ratios, effect of colonisation, lack of knowledge and information, access and poverty barriers, relationship with health professionals, illness perceptions, treatment beliefs and Whaakaro (thoughts), and beliefs pertaining to natural (rongoā) and Western medicine. Participants identified potential solutions to improve antibiotic use such as cultural support and involving Te Ao Māori; recognising these can inform future AMS initiatives.